Development of an Initial Teaching Factory Model Based on ‎Cippo Evaluation to Improve Employability Skills and ‎Creativity of SMK Students in The Fashion Design and ‎Production Expertise Program - Hamlaini Hamlaini (Yayasan Darussalam Bengkulu, 2026)
This study aims to develop an initial Teaching Factory model based on CIPPO (Context, Input, Process, Product, Outcome) evaluation to improve employability skills and creativity of vocational high school (SMK) students majoring in Fashion Design and Production at SMKN 2 Ogan Komering Ulu. The research employed Research and Development (R&D) method using the ADDIE model. Data were collected through questionnaires, observation, in-depth interviews, and product assessments. The research subjects were 45 eleventh-grade students of the Fashion Design and Production Study Program. Model validation was conducted by curriculum experts, fashion industry practitioners, and educational evaluation experts. The results indicate that: (1) the CIPPO-based Teaching Factory model developed was declared valid by experts with a mean score of 4.38 out of 5 (very good category); (2) there was a significant improvement in students' employability skills with a normalized gain score of 0.62 (medium category); (3) students' creativity scores improved significantly from an average of 64.2 to 82.7 (28.8% increase); (4) CIPPO evaluation identified relevant contextual, input, process, product, and outcome factors in the implementation of Teaching Factory. This model provides a systematic framework that integrates the needs of the fashion industry with real production-based learning, making it relevant for implementation in vocational schools throughout Indonesia.